Hardness of Hydroxyapatite-Based Scaffolds Derived from Green Mussel Shells at Various Gelatin Concentrations - Ikhya Ulumuddin; Widi Widiyat (Journal of Creativity Student, 2026)
Large-sized bone defects require scaffolds capable of supporting tissue regeneration while possessing adequate mechanical characteristics. This study aims to analyze the effect of varying gelatin compositions on the hardness characteristics of hydroxyapatite-based scaffolds synthesized from green mussel shells (Perna viridis). Hydroxyapatite was synthesized using calcium precursors derived from calcined green mussel shells and subsequently characterized using X-Ray Diffraction (XRD). The scaffolds were fabricated using the slurry casting method with gelatin composition variations of 2%, 3%, and 4%, alongside hydroxyapatite compositions of 98%, 97%, and 96%, respectively. The mechanical characteristics of the scaffolds were tested using a Copley TBF 1000 Tablet Hardness Tester to obtain the breaking force values. The XRD results demonstrated that the synthesized material was dominated by a hydroxyapatite phase with a weight percentage of 98.7%, while the calcite and portlandite phases were 1.0% and 0.3%, respectively. The testing results indicated that the commercial scaffold exhibited the highest breaking force value of 3.51 kg. For the green mussel shell scaffolds, the highest value was obtained at the 2% gelatin variation at 1.37 kg, followed by 4% gelatin at 0.96 kg, and 3% gelatin at 0.69 kg. After conversion using the ASTM C496 equation, the mechanical value of the commercial scaffold was 0.609 MPa, whereas the 2%, 3%, and 4% gelatin variations were 0.238 MPa, 0.120 MPa, and 0.130 MPa, respectively. All of these values remained below the mechanical requirement of ≥1.5 MPa. Thus, the variation in gelatin composition influenced the mechanical characteristics of the scaffolds in a non-linear manner. The 2% gelatin composition produced the best mechanical characteristics compared to the other variations; however, it still requires further development to meet the mechanical requirements for bone graft materials.